Molecular Transporter System For Qubits Generation - I. S. Amiri; A. Afroozeh; M. Bahadoran; J. Ali; P. P. Yupapin (My University, 2012)
A molecular cryptography technique using optical tweezers, is proposed. The optical tweezer transports the molecules in the communication system. The optical tweezer generated by the dark soliton is in the form of a potential well. The dark soliton propagates inside nonlinear microring resonator (NMRR). Transportation of molecules is implemented when the dark soliton is used as input pulse. The input bright soliton control the output signal at the drop port of the system. Output optical tweezers can be connected to the quantum signal processing system consisting of transmitter and the receiver. The transmitter is used to generate the high capacity quantum codes within the series of MRR’s and an add/drop filter. The receiver will detect the encoded signals known as quantum bits. The transmitter will generate the entangled photon pair which propagates via an optical communication link. Here the smallest optical tweezer with respect to the full width at half maximum FWHM is 17.6 nm in the form of potential well is obtained and transmitted through quantum signal processor via an optical link. Key words: Internet security; optical tweezers; quantum cryptography; quantum signal processing; entangled photon pair
Keywords: Quantum Information and Cryptography